An Analysis of Factors Affecting Low Literacy in Primary School Students: A Systematic Literature Review - Mela Purnama Dewi; Elizar (Universitas Pendidikan Ganesha, 2026)
Low reading and writing skills among elementary school students remain a critical issue as they affect the quality of learning and the development of broader academic competencies, including analytical thinking and problem-solving skills. This study aims to analyze and integrate various factors contributing to low literacy among elementary school students using a Systematic Literature Review approach. The study employs secondary data in the form of scientific articles retrieved from the Google Scholar database, with inclusion criteria of articles published between 2020–2024, available in full text, and focused on basic literacy. The selection process was conducted through systematic stages of identification, screening, and eligibility assessment by two independent reviewers to enhance result validity. A total of ten selected articles were analyzed using descriptive qualitative analysis to identify patterns and relationships among factors. The findings indicate that low literacy is influenced by the interaction of internal factors, such as cognitive readiness, motivation, and learning interest, as well as external factors, including family support, learning quality, availability of reading materials, and social environment. These findings emphasize that basic literacy is the result of multidimensional and interrelated interactions. Therefore, literacy improvement requires an integrated, sustainable strategy that is aligned with learners’ developmental contexts. This study implies the importance of strengthening collaboration between families and schools, as well as improving the quality of literacy instruction.